2008
DOI: 10.1158/1535-7163.mct-08-0015
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase inhibition results in a magnetic resonance–detectable drop in phosphocholine

Abstract: Expression of fatty acid synthase (FASN), the key enzyme in de novo synthesis of long-chain fatty acids, is normally low but increases in cancer. Consequently, FASN is a novel target for cancer therapy. However, because FASN inhibitors can lead to tumor stasis rather than shrinkage, noninvasive methods for assessing FASN inhibition are needed. To this end, we combined 1 H, 31 P, and 13 C magnetic resonance spectroscopy (MRS) (a) to monitor the metabolic consequences of FASN inhibition and (b) to identify MRS-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Interestingly, a reduction in cellular PC content and ChoK activity is also observed with the MEK inhibitors U0126 52 and PD059001 53 and following FASN inhibition with orlistat and cerulenin, 71 suggesting a degree of regulatory overlap between proteins such as PI3K, MEK and FASN over PC homeostasis. This is perhaps unsurprising given the multiplicity of cellular Furthermore, a decline in levels of PC and PtdCho detected by 1 H, 31 P and 13 C MRS was also observed that was linked to ChoK inhibition.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, a reduction in cellular PC content and ChoK activity is also observed with the MEK inhibitors U0126 52 and PD059001 53 and following FASN inhibition with orlistat and cerulenin, 71 suggesting a degree of regulatory overlap between proteins such as PI3K, MEK and FASN over PC homeostasis. This is perhaps unsurprising given the multiplicity of cellular Furthermore, a decline in levels of PC and PtdCho detected by 1 H, 31 P and 13 C MRS was also observed that was linked to ChoK inhibition.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 92%
“…FASN is a key enzyme for the de novo formation of fatty acids from glycolytic intermediates, and its expression is increased in various human cancer types correlating with poor prognosis thus making it a promising target for mechanism-based cancer treatment. 28,70 Treatment with the FASN inhibitor orlistat reduced the proliferation of human prostate, breast and ovarian carcinoma cells and inhibited FASN activity leading to a decline in levels of fatty acids formed from 13 C-labeled glucose, as detected by 13 C MRS. 71 carcinoma cells in vitro and in vivo. 59 This effect was attributed to a decline in LDH-A activity as well as LDH-A and HIF1 protein expression.…”
Section: Metabolic Biomarkers Of Drugs Targeted At Signal Transductiomentioning
confidence: 99%
“…As aberrant BCR promotes the expression of the proglycolytic protein C-MYC (Mahon et al, 2003), decreased glycolysis in response to imatinib treatment could be mediated through C-MYC suppression. Inhibition of FASN with Orlistat resulted in a decrease in NTP and PCr levels (Ross et al, 2008). FASN can be activated by PI3K and RAF-MEK-ERK1/2 signalling, which suggests that the effects on bioenergetics resulting from Orlistat treatment could be mediated through alterations in either PI3K or MEK-ERK1/2 signalling.…”
Section: Choline Phospholipid Metabolismmentioning
confidence: 94%
“…Hence, the role of ChoK in the MRS-detectable changes in PC after treatment with targeted drugs was investigated. The decrease in PC levels after inhibition of FASN with Orlistat has been attributed to the inhibition of its synthesis as a result of a reduction in ChoK activity (Ross et al, 2008). As both FASN (Yang et al, 2002) and ChoK (Ramírez de Molina et al, 2002) are regulated by MEK-ERK1/2 and PI3K, ChoK could be involved in PC reduction following inhibition of these pathways.…”
Section: Choline Phospholipid Metabolismmentioning
confidence: 99%
“…Thus the expression of asparaginase depletes the availability of asparagine because it degrades it to aspartate [194]. The same concept of depletion applies to more recently found inhibitors of fatty acid synthase or choline kinase [198,199], which are in various (pre)clinical phases. Thereby, the concept of depletion goes always along with the risk that either the metabolites that are synthesized can be taken up from the environment or that the pathway is also essential for nontumorigenic cells.…”
Section: Therapeutic Opportunities Of Cancer Metabolismmentioning
confidence: 98%